The conundrum of acute onset midline neck swellings: a unique case report of a thyroid abscess - Shetti, Preeti; Vasudevan, Chenchulakshmi; Amin, Dhawal (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
The conditions of the thyroid gland are the most common causes for midline neck swellings and present with a spectrum of clinical features and differential diagnosis, some more fatal than the others. One such rare yet worrisome condition is suppurative thyroiditis progressing to an abscess. A 17 year old male presented with an acute neck swelling with fever, pain, and hoarseness of voice. Investigations revealed leucocytosis with normal thyroid hormone levels. Contrast enhanced CT scan of the neck showed presence of an abscess of the thyroid gland with left sided tracheal shift. Incision and drainage with antibiotic support was done leading to an uneventful recovery. The thyroid gland by virtue of its capsule, rich blood supply, and high iodine content is resistant to infection. Thyroid abscess is a rare condition with high morbidity and mortality. This condition should be a differential diagnosis in cases of acute onset midline swellings. Immediate surgical drainage of the collection with antibiotic support is the gold standard treatment of this condition.